2018
DOI: 10.14744/eej.2018.03522
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different post luting cements on the fracture strength of endodontically treated teeth: An in vitro study

Abstract: To evaluate the fracture resistance of endodontically treated mandibular premolars restored with glass fiber posts using different luting agents. Methods: Twenty-four extracted single-rooted mandibular premolars were endodontically treated, and post spaces were prepared to receive fiber posts. They were assigned to three test groups (n=8) according to the type of cement used for the cementation of glass fiber posts: RC group: adhesive resin cement group (etch and rinse), SC group: self-adhesive resin cement gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Moreover, there is usually just one root on the mandibular premolars [ 3 ]. Mandibular premolars have also been used in a number of research studies to evaluate the fracture resistance of the post system and have been considered suitable for this purpose [ 5 , 15 , 16 ]. Since the dimension of the teeth was shown to be a crucial factor in the specimen's ability to withstand fracture, it was meticulously chosen for this research to be uniform [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is usually just one root on the mandibular premolars [ 3 ]. Mandibular premolars have also been used in a number of research studies to evaluate the fracture resistance of the post system and have been considered suitable for this purpose [ 5 , 15 , 16 ]. Since the dimension of the teeth was shown to be a crucial factor in the specimen's ability to withstand fracture, it was meticulously chosen for this research to be uniform [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular premolars were selected in this study as they are most susceptible to root fracture and used in previous studies. [ 13 ] To mimic clinical conditions, NaOCl was used for canal irrigation. Although NaOCl is reported to compromise bond strengths of the adhesive systems to canal dentine, Nova et al [ 15 ] observed that NaOCl irrigation did not decrease the bond strength of self-etch or self-adhesive resin cement to a nonacceptable clinical level.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this explains the ease of Contec Blanco post removal irrespective of the cement type. Samran et al [ 13 ] reported that additional dentine conditioning step in adhesive cement (total etch) achieved greater bond strength than self-adhesive cement due to formation of a dentine-post monobloc system and this was a determining factor for fracture resistance. Similarly, Zicari et al [ 24 ] found that self-etching 10-methacryloyloxydecyl dihydrogen phosphate-based cements presented the highest push-out bond strength as compared with self-adhesive cements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations